2013
DOI: 10.1097/mot.0b013e32835e2a1b
|View full text |Cite
|
Sign up to set email alerts
|

Machine perfusion viability testing

Abstract: Machine perfusion characteristics and perfusate biomarkers have been extensively studied. They often correlate with the transplant outcome, but the present viability tests are not reliable predictors of transplant outcome. New developments in kidney graft viability assessment are necessary to have a chance of being clinically useful in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Machine preservation characteristics are commonly used for graft selection of DBD and DCD kidneys; however, the level of evidence of the benefits of this selection is usually poor. Results are often biased, as kidneys with high intrarenal resistance are not transplanted . Two studies, in which kidneys were transplanted irrespective of intrarenal resistance, one including both DBD and DCD kidneys and the other DCD kidneys only, showed that intrarenal resistance was an independent risk factor for PNF, DGF and 1‐year graft survival .…”
Section: Preservation Of Dcd Kidneysmentioning
confidence: 99%
“…Machine preservation characteristics are commonly used for graft selection of DBD and DCD kidneys; however, the level of evidence of the benefits of this selection is usually poor. Results are often biased, as kidneys with high intrarenal resistance are not transplanted . Two studies, in which kidneys were transplanted irrespective of intrarenal resistance, one including both DBD and DCD kidneys and the other DCD kidneys only, showed that intrarenal resistance was an independent risk factor for PNF, DGF and 1‐year graft survival .…”
Section: Preservation Of Dcd Kidneysmentioning
confidence: 99%
“…renal grafts for transplantation 22. Other studies investigated machine perfusate biomarkers, such as LDH and AST (nonspecific markers of cellular injury), glutathione-S-transferase (a renal tubular enzyme, associated with proximal tubular injury), N-acetylβd-glucosaminidase, heart-type fatty acid binding protein, redox-active iron, interleukin-18, lipid peroxidation products, neutrophil gelatinase-associated lipocalin, and ionized calcium 3,23. Similar to IRR, some perfusate biomarkers correlate with posttransplantation renal function such as DGF 24 but do not represent stand-alone tools for acceptance or rejection of renal grafts for transplantation.Stubenitsky and colleagues developed a renal graft perfusion system called exsanguinous metabolic support for graft storage and repair at near-physiologic temperatures of 32°C 25.…”
mentioning
confidence: 99%
“…Subsequent analyses of the trial found high renal resistance at the end of machine perfusion to be an independent risk factor for both DGF and 1-year graft failure (32). As other investigators have also suggested (33), additional studies are urgently needed to discern the role of perfusion parameters in the decision process for allograft selection and organ discard, and we believe the potential utility of perfusate biomarkers of kidney injury deserves further investigation as well. Perfusate biomarkers were natural log-transformed and added individually to all models (i.e.…”
Section: Perfusate Gst and Dgfmentioning
confidence: 91%